Numerical simulation of backward erosion piping in heterogeneous fields. Issue 4 (19th April 2017) - Liang, Yue; Yeh, Tian‐Chyi Jim; Wang, Yu‐Li; Liu, Mingwei; Wang, Junjie; Hao, Yonghong
Abstract: Backward erosion piping (BEP) is one of the major causes of seepage failures in levees. Seepage fields dictate the BEP behaviors and are influenced by the heterogeneity of soil properties. To investigate the effects of the heterogeneity on the seepage failures, we develop a numerical algorithm and conduct simulations to study BEP progressions in geologic media with spatially stochastic parameters. Specifically, the void ratio e, the hydraulic conductivity k, and the ratio of the particle contents r of the media are represented as the stochastic variables. They are characterized by means and variances, the spatial correlation structures, and the cross correlation between variables. Results of the simulations reveal that the heterogeneity accelerates the development of preferential flow paths, which profoundly increase the likelihood of seepage failures. To account for unknown heterogeneity, we define the probability of the seepage instability (PI) to evaluate the failure potential of a given site. Using Monte‐Carlo simulation (MCS), we demonstrate that the PI value is significantly influenced by the mean and the variance of ln k and its spatial correlation scales. But the other parameters, such as means and variances of e and r, and their cross correlation, have minor impacts. Based on PI analyses, we introduce a risk rating system to classify the field into different regions according to risk levels. This rating system is useful for seepage failures prevention and assists decision making when BEP occurs. Key Points: Proposing a numerical approach that involves the heterogeneity of soils in simulating of back erosion piping Interpreting the influences of the uncertainty and the spatial variability of soil properties Introducing the risk rating system to classify the field into regions according to different risk levels